2010
DOI: 10.1007/s11033-010-0615-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological role of MicroRNA-103 based on expression profile and target genes analysis in pigs

Abstract: MicroRNAs (miRNAs) are endogenously expressed RNAs consisting of 20-24 nucleotides. These molecules are thought to repress protein translation by binding to target mRNAs. However, biological functions have not been assigned to most of the 175 porcine miRNAs registered in miRBase (release 15.0). In an effort to uncover miR-103 important in pigs, we examined the integrative tissue expression profile and gene ontology (GO) term enrichment of predicted target genes to determine the global biological functions of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…As shown in Supplementary Fig. 2, the expression of the PPARg targets miR-103 and miR-107, which have previously been demonstrated to be induced during differentiation, was up-regulated in Lkb1-shRNA-expressing cells, particularly in the late stages of differentiation (day 6; Esau et al 2004, Li et al 2011. Interestingly, the expression of Cebpd was significantly higher in Lkb1-shRNA-expressing cells 30 min after the induction of differentiation (Fig.…”
Section: Lkb1 Depletion Facilitates 3t3-l1 Adipocyte Differentiationsupporting
confidence: 52%
“…As shown in Supplementary Fig. 2, the expression of the PPARg targets miR-103 and miR-107, which have previously been demonstrated to be induced during differentiation, was up-regulated in Lkb1-shRNA-expressing cells, particularly in the late stages of differentiation (day 6; Esau et al 2004, Li et al 2011. Interestingly, the expression of Cebpd was significantly higher in Lkb1-shRNA-expressing cells 30 min after the induction of differentiation (Fig.…”
Section: Lkb1 Depletion Facilitates 3t3-l1 Adipocyte Differentiationsupporting
confidence: 52%
“…For fat traits, miR-103 and miR-107 were highly correlated (Table 3). This is consistent with previous reports of miR-103 being involved in adipogenesis, lipid metabolism, and adipocyte differentiation [54,55] and of miR-103/107 being involved in glucose homeostasis and insulin sensitivity [56]. …”
Section: Discussionsupporting
confidence: 93%
“…Previous studies demonstrated that miR-103 was involved in various biological processis such as brain development, adipocyte differentiation, lipid metabolism, hematopoiesis, and immunity [55][58]. A recent study has reported that miR-103 also expressed in testis of piglets but not in adult pig testis, which indicates that miR-103 expression pattern depends on the developmental stages of pigs and may have important biological roles in testis [8]. miR-202-5p was highly expressed in adult human testis, which is consistent with the observation in mouse testis [6].…”
Section: Discussionmentioning
confidence: 97%